2022
DOI: 10.1021/acsami.2c06998
|View full text |Cite
|
Sign up to set email alerts
|

Facile Approach to Enhance Activity and CO2 Resistance of a Novel Cobalt-Free Perovskite Cathode for Solid Oxide Fuel Cells

Abstract: Developing high-performance and cost-effective cathodes is ever-increasingly vital for the advancement of intermediate-temperature solid oxide fuel cells (IT-SOFCs). To facilitate the popularization of nonprecious metallic and cobalt-free oxygen reduction electrodes, herein, we propose a novel perovskite-based BaFeO3−δ (BF) matrix, Ba0.75Sr0.25Fe0.875Y0.125O3−δ (BSFY), as a highly active cathode for IT-SOFCs. To our satisfaction, the BSFY electrode showcases a low area-specific resistance of 0.063 Ω cm2, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…, all of which have demonstrated increased resistance to CO 2 poisoning. 62,85–91 The above investigations underscore the promising potential of multi-cation synergy in developing highly CO 2 -resistant cathode candidates.…”
Section: Evaluation Methods For Co2 Tolerance In Perovskite Cathodesmentioning
confidence: 91%
See 2 more Smart Citations
“…, all of which have demonstrated increased resistance to CO 2 poisoning. 62,85–91 The above investigations underscore the promising potential of multi-cation synergy in developing highly CO 2 -resistant cathode candidates.…”
Section: Evaluation Methods For Co2 Tolerance In Perovskite Cathodesmentioning
confidence: 91%
“…This approach enables the BSFY electrode to showcase impressive CO 2 -tolerance with an ultralow deterioration rate of ∼0.00011 Ω cm 2 min −1 , surpassing that of a great majority of reported CO 2 -resistant perovskite analogues. 86 Seeking further enhancement, we formulated a composite cathode with a nominal composition of Bi 0.7 Pr 0.1 Ba 0.2 FeO 3− δ (BPBF) and SDC for short-term contaminant poisoning tests. Encouragingly, the BPBF-based electrode performs stably with a constant electroactivity of 0.31 Ω cm 2 at 600 °C over a 50 h period, suggesting its significant potential as a practical air electrode material.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of cathode modification methods have been proposed to promote electrochemical performance, including element doping, defect regulation, surface decoration, and composite engineering. [17][18][19][20] Studies have revealed that the catalytic properties of perovskite oxides for ORR are closely associated with oxygen vacancies, which have a significant impact on the crystal structure, electronic properties, as well as surface chemistry of the materials. [21] The defect regulation at the A-or Bsite is valued as the most direct and feasible strategy to tune the oxygen vacancies in typical perovskite oxides.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In retrospect, numerous perovskite-type oxides with mixed ionic-electronic conducting nature have been employed for oxygen-ion conducting SOFCs (O-SOFCs), as well as proton conducting SOFCs (H-SOFCs). [8][9][10][11][12] Unlike the traditional pure electronic conductor where the reaction active sites only locate at the threephase boundary, mixed ionic-electronic conducting perovskites can extend the active area to entire phase surface, thereby achieving desirable oxygen reduction reaction (ORR) activity. [13,14] Some highly promising electrode materials have been reported with exclusivity for O-SOFCs or H-SOFCs, however, up to now, there is a lack of highly efficient bifunctional electrodes for both SOFCs owing to the difference in cathode reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%